Reduced Levels of NAD in Skeletal Muscle and Increased Physiologic Frailty Are Associated With Viral Coinfection in Asymptomatic Middle-Aged Adults. (1st February 2022) - Tran, Thanh; Pencina, Karol M.; Schultz, Michael B.; Li, Zhuoying; Ghattas, Catherine; Lau, Jackson; Sinclair, David A.; Montano, Monty
Abstract : Background: People living with HIV (PLWH) are disproportionately burdened with multimorbidity and decline in physiologic function compared with their uninfected counterparts, but biological mechanisms that differentially contribute to the decline in muscle function in PLWH compared with uninfected people remain understudied. Setting: The study site was Brigham and Women's Hospital, Harvard Medical School, Boston, MA. Methods: We evaluated skeletal muscle tissue for levels of total nicotinamide adenine dinucleotide (NAD), NAD +, and nicotinamide adenine dinucleotide (NADH) in middle-aged asymptomatic PLWH, coinfected with hepatitis C virus and/or cytomegalovirus and compared them with uninfected control participants. Results: Of the 54 persons with muscle biopsy data, the mean age was 57 years with 33% women. Total NAD levels declined in skeletal muscle in association with HIV infection and was exacerbated by hepatitis C virus and cytomegalovirus coinfection, with lowest levels of total NAD, NAD +, and NADH among persons who were coinfected with all 3 viruses ( P = 0.015, P = 0.014, and P = 0.076, respectively). Levels of total NAD, NAD +, and NADH in skeletal muscle were inversely associated with inflammation ( P = 0.014, P = 0.013, and P = 0.055, respectively). Coinfections were also associated with measures of inflammation (CD4/CD8 ratio: P < 0.001 and sCD163: P < 0.001) and immune activation (CD38 and human leukocyte antigen-DR expression on CD8 T cells: P < 0.001). In addition, coinfection was associated with increased physiologic frailty based on the Veteran Aging Cohort Study 1.0 index assessment ( P = 0.001). Conclusions: Further research is warranted to determine the clinical relevance of preclinical deficits in NAD metabolites in skeletal muscle in association with viral coinfection and inflammation, as well as the observed association between viral coinfection and physiologic frailty.